Haemodynamic forces predicting remodelling and outcome in patients with heart failure treated with sacubitril/valsartan - Iacopo Fabiani; Nicola Riccardo Pugliese; Gianni Pedrizzetti; Giovanni Tonti; Vincenzo Castiglione; Vladislav Chubuchny; Claudia Taddei; Alessia Gimelli; Lavinia Del Punta; Alessio Balletti; Annamaria Del Franco; Stefano Masi; et al. (ESC Heart Failure, 2023)
Abstract Aims A novel tool for the evaluation of left ventricular (LV) systo‐diastolic function through echo‐derived haemodynamic forces (HDFs) has been recently proposed. The present study aimed to assess the predictive value of HDFs on (i) 6 month treatment response to sacubitril/valsartan in heart failure with reduced ejection fraction (HFrEF) patients and (ii) cardiovascular events. Methods and results Eighty‐nine consecutive HFrEF patients [70% males, 65 ± 9 years, LV ejection fraction (LVEF) 27 ± 7%] initiating sacubitril/valsartan underwent clinical, laboratory, ultrasound and cardiopulmonary exercise testing evaluations. Patients experiencing no adverse events and showing ≥50% reduction in plasma N‐terminal pro‐B‐type natriuretic peptide and/or ≥10% LVEF increase over 6 months were considered responders. Patients were followed up for the composite endpoint of HF‐related hospitalisation, atrial fibrillation and cardiovascular death. Forty‐five (51%) patients were responders. Among baseline variables, only HDF‐derived whole cardiac cycle LV strength (wLVS) was higher in responders (4.4 ± 1.3 vs. 3.6 ± 1.2; p = 0.01). wLVS was also the only independent predictor of sacubitril/valsartan response at multivariable logistic regression analysis [odds ratio 1.36; 95% confidence interval (CI) 1.10–1.67], with good accuracy at receiver operating characteristic (ROC) analysis [optimal cutpoint: ≥3.7%; area under the curve (AUC) = 0.736]. During a 33 month (23–41) median follow‐up, a wLVS increase after 6 months (ΔwLVS) showed a high discrimination ability at time‐dependent ROC analysis (optimal cut‐off: ≥0.5%; AUC = 0.811), stratified prognosis (log‐rank p < 0.0001) and remained an independent predictor for the composite endpoint (hazard ratio 0.76; 95% CI 0.61–0.95; p < 0.01), after adjusting for clinical and instrumental variables. Conclusions HDF analysis predicts sacubitril/valsartan response and might optimise decision‐making in HFrEF patients.